2023
DOI: 10.1111/1467-8500.12584
|View full text |Cite
|
Sign up to set email alerts
|

The role of authentic leadership on healthcare Street‐Level Bureaucrats’ well‐being during the pandemic

Abstract: This study uses Conservation of Resources Theory, to explain Street‐Level Bureaucrats’ (SLBs) workplace behavioural responses to threats to their well‐being. We examine whether authentic leadership within street‐level organisations positively impacts employee well‐being by increasing SLBs’ perception of personal resources, and reducing their perceptions of work harassment. The research design comprises a survey that solicited quantitative and qualitative data from 163 healthcare SLBs working in Australian hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
1
5
0
1
Order By: Relevance
“…Mental health problems are common and often remain untreated, as was also found by scholars analyzing other street-level bureaucrats working during the pandemic (e.g. Brunetto et al, 2022;Farr-Wharton et al, 2022;Salehi et al, 2023). In our cases we found that, in response to untreated mental health issues, workers often develop fatalist or cynical attitudes regarding their work.…”
supporting
confidence: 84%
See 3 more Smart Citations
“…Mental health problems are common and often remain untreated, as was also found by scholars analyzing other street-level bureaucrats working during the pandemic (e.g. Brunetto et al, 2022;Farr-Wharton et al, 2022;Salehi et al, 2023). In our cases we found that, in response to untreated mental health issues, workers often develop fatalist or cynical attitudes regarding their work.…”
supporting
confidence: 84%
“…However, this pattern does not seem to result simply from maximizing, selfish, or opportunistic calculations by frontline workers, but is, rather, a product of the conditions in which they are bound to operate. Moreover, considering that behavioral responses affect wellbeing (Salehi et al, 2023), we can expect that, in extreme cases as those analyzed here, the self-preservation response emerges as a survival strategy. This conclusion helps explain why studies in non-Western countries often find that street-level bureaucrats simultaneously exclude clients (Eiró, 2019;Perelmiter, 2021;Spink et al, 2021) and try to bridge significant public service gaps (Masood & Nisar, 2021;Mohammed, 2021).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Adanya pandemi COVID-19 yang belum lama ini terjadi, penelitian yang menaikkan isu-isu yang berkaitan dengan tenaga kesehatan banyak dilakukan (Awad & Ashour, 2022;Salehi et al, 2023).…”
Section: Pendahuluanunclassified